Effect of Carbohydrate Counting with Telephone Follow-up on Blood Glucose Parameters in Type 2 Diabetic Patients at Phaholpolphayuhasena Hospital, Kanchanaburi Province - Boonjun, Susheela; Pongpatanawut, Supawan (Journal of Nutrition Association of Thailand (Online), 2018)
Diabetes is a major public health problem in Thailand and it results in increasing trend of mortality rate every year. The consumed diet remarkably affects blood sugar levels in diabetic patients. Carbohydrate counting is one approach to assist the patient in controlling amount of food intakes and then blood sugar level can be controlled. Moreover, following up by phone calls can encourage a patient cooperation in food control. This study aims to measure effects of general nutritional advice comparing with carbohydrate counting advice plus 2 week follow up telephone on the blood sugar levels in type 2 diabetic patients. The eligible subjects ,who had age of 20-60 year, HbA1c 7-9% with at least 1 year diabetes diagnosis, reading capability, no medication dose adjustment for 6 consecutive months and capable use of telephone communication, were randomized to general nutritional advice (control) group and carbohydrate counting advice with 2 week follow up phone calls (study) group. The data were collected for 6 months and the blood glucose was gathered at 0, 3rd, and 6th months. The statistical analysis was independent simple t- test. There were 43 subjects in control group and 46 subjects in study group. The results showed that the differentiation of HbA1C blood glucose levels at 0 and 6th months were significantly lower in the study group than in the control group (p-value < 0.001). The fasting blood sugar (FBS) levels at 0 and 6th months were also significantly lower in the study group than in the control group (p-value = 0.024). This study showed that the carbohydrate counting advice with follow-up calls helped diabetic patients for a better control of their blood glucose levels. Control diet in diabetic patients via carbohydrate counting is recommended for menu selection and controlling blood sugar.